If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6y-8=-y+12+2y
We move all terms to the left:
6y-8-(-y+12+2y)=0
We add all the numbers together, and all the variables
6y-(y+12)-8=0
We get rid of parentheses
6y-y-12-8=0
We add all the numbers together, and all the variables
5y-20=0
We move all terms containing y to the left, all other terms to the right
5y=20
y=20/5
y=4
| 4(5x+5)=-5(5x-5)-2x | | -.75z+1=-8 | | 12p-6p=18 | | 3(=1)=4b-1 | | 12p−6p=18 | | x+20+7x=100 | | 18x+1/2=6(3x+25 | | 10k-8=2(4k+2) | | -3x+1=4x-55-7 | | 63-p=46 | | 11/3k=1/3 | | w=6=2(w-6) | | 514-11x=17x+10 | | 7(2-3x)=5-9 | | 11(x+10)=136 | | (x-3)2=9x | | 2x-14=5x-4 | | 48-15v=-12v+18 | | 5(2d=4)=35 | | X+5x-180=180 | | 9x-19=2(3x-2) | | -7/12k+3/8=-5/4 | | 4x-6+7=2x+11 | | -(x-5)=2x-5x-3 | | .5n-19=-14 | | 5/x+4=4/3x+25/6 | | -5(-4x-3)=155 | | 6z+15=51 | | 6x+8=x-14 | | 7e+11=e+143 | | 6.1g+8=3.1g+14 | | 8d+2=182+6d |